Patterns of Online Media Content suaramuhammadiyah.id during the General Election Campaign 2024 - Romadlan, Said; Maududi, Mukhlish Muhammad (Jogjakarta Communication Conference (JCC), 2024)
Patterns of media content are the continuous tendency of a media to report an issue that is associated with certain interests or ideologies. The focus of this research is on how the patterns of online media content Suaramuhammadiyah.id during the 2024 election campaign? The method used is qualitative content analysis. The results showed that patterns of online media content Suaramuhammadiyah.id highlighted the issue of the role of women voters and Muhammadiyah cadres in the 2024 election. The resource persons used were more dominant among Muhammadiyah internal circles, especially women, and academicians. While the tendency of the content is neutral, do not take sides with one of the candidates for president and vice president. The patterns of online media content suaramuhammadiyah.id are influenced by the ideology of moderatism which can be seen from the tendency of neutral content. The results of this study emphasize the important role of suaramuhammadiyah.id as a medium for spreading moderate Islamic understanding as contained in the doctrine of Progressive Islam.